Walking in Balance: Native American Recovery Programmes - Owen, Suzanne (Religions, 2014)
This article reviews Native American ritual practices, frameworks and key concepts employed by several substance abuse treatments centres in the U.S. and Canada. It also examines the way Alcoholics Anonymous’ Twelve Step programme has been modified to attract and serve the needs of Native Americans and First Nations and its potential impact on the ritual practices. Native concepts of wellbeing are highlighted and linked to the idea of living in “balance”.